PERUVIAN INTERNATIONAL TRADE VULNERABILITY IN THE CURRENT GLOBAL CONTEXT - Bouby Tolentino, Francisca (2016)
The liberalization process of the Peruvian economy, initiated in the 1990s, has led the external sector to a high level of vulnerability in the current global context. On the one hand, the rapid growth of exports -mainly primary products- is linked to the price increase due to China’s strong demand, starting in the 2000s. However, the international crisis of 2008-2009 and the beginning of the Chinese economic model change, had an impact on the process decline of Peruvian exports since 2012; accentuated by the sharp fall in raw material prices and the loss of competitiveness vis-à-vis Asian products. On the other hand, the structure and composition of Peruvian international trade, including a pattern of specialization oriented to the export of low added value goods and the growing import of high and medium technology goods, represent one of the major weaknesses of the national economy.